2008
DOI: 10.1007/s00436-008-1101-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative karyological analysis of three members of Allocreadiidae (Digenea): taxonomic and phylogenetic implications

Abstract: Chromosome number and morphology were studied in three allocreadiid species from mitotic metaphases of intramolluscan stages using karyometric analysis. Bunodera luciopercae has a diploid number 2n=14, with two large pairs of metacentrics, one pair of submeta-subtelocentrics, and four pairs of acrocentrics. Karyotype of Allocreadium isoporum, 2n=14, with two large pairs of metacentrics and five pairs of acrocentrics was recognized to be closely related to that of B. lucioperca. The most conspicuous interspecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…In that family, the species studied until now have acrocentric, submetacentric and metacentric chromosomes. The present results provide new data and complement the description made by Petkevičiute & Stanevičiute (2008) about the karyotype homogeneity respect the number, morphology and number of chromosomes in these two close families.…”
Section: Discussionsupporting
confidence: 88%
“…In that family, the species studied until now have acrocentric, submetacentric and metacentric chromosomes. The present results provide new data and complement the description made by Petkevičiute & Stanevičiute (2008) about the karyotype homogeneity respect the number, morphology and number of chromosomes in these two close families.…”
Section: Discussionsupporting
confidence: 88%
“…There are numerous cases of the detection of cryptic species with narrow host specificity within well-known generalist parasites (see Combes, 2001). Recent surveys based on morphology, random amplification of polymorphic DNA (RAPD) profiles, host specificity, karyology and DNA sequences (Sokolov et al , 2006; Petkevičiūtė & Stanevičiūtė, 2008; Petkevičiūtė et al , 2010) revealed the existence of a morphologically similar species complex within the allocreadiid B. luciopercae (Müller, 1776).…”
Section: Discussionmentioning
confidence: 99%
“…But 56 chromosomes were found in diploid sets of Clonorchis sinensis (Park et al , 2000). Allocreadiid species possess comparatively large chromosomes, up to 13–14 μm, but low haploid numbers of six, seven or eight were recorded in most species (for a review see Petkevičiūtė & Stanevičiūtė, 2008). The chromosome complement of C. crassum is unusual among digeneans due to the low number, 2 n = 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the chromosome sets composed of 22 or 20 elements are characteristic for the great majority of trematode species. Diploid number 2n = 14 is less common between digeneans but it was revealed in species of some unrelated families such as Paramphistomidae Fischoeder, 1901, Bucephalidae Poche, 1907, Echinochasmidae Odhner, 1910, Allocreadiidae Looss, 1900 or Opisthorchiidae Looss, 1899 (Baršienė, 1993; Petkevičiūtė & Stanevičiūtė, 2008; Petkevičiūtė et al, 2014). From the new data on the karyotypes of lissorchiids, it is obvious that representatives of some families of trematodes can demonstrate varying degrees of chromosomal diversification, sharing conservative and highly derived karyotypes.…”
Section: Discussionmentioning
confidence: 99%